Self‐Cleaning: Engineering Fully Organic and Biodegradable Superhydrophobic Materials (Adv. Mater. Interfaces 1/2019). Issue 1 (10th January 2019) - Milionis, Athanasios; Sharma, Chander Shekhar; Hopf, Raoul; Uggowitzer, Michael; Bayer, Ilker S.; Poulikakos, Dimos
Abstract : In article number1801202 by Athanasios Milionis, Dimos Poulikakos and co‐workers develop a fully organic and biodegradable material with self‐cleaning behavior. The self‐cleaning properties are demonstrated by allowing contaminant powder to cover the surface, to eventually be removed by impacting water drops. Given its sustainable composition, the demonstrated material can reasonably sustain its wettability properties under water drop and jet impact, and folding tests. Such a bio‐inspired and biodegradable material system is advancing the state of the art of future‐oriented sustainable materials. The cover image shows simultaneously the natural Lotus leaf and its transformation to its man‐made artificial counterpart. Both materials (artificial and natural) share similar basic chemical composition (cellulose and wax) and their surface topography comprises cellulose hierarchical micropapillae, uniformly covered with wax.